1986
DOI: 10.1111/j.1365-2141.1986.tb04119.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the plasma cell labelling index with bromodeoxyuridine in a double fluorescence technique

Abstract: A new technique is described in which plasma cells actively synthesizing DNA can be identified in a heterogeneous cell population such as bone marrow. This method uses bromodeoxyuridine (BrdU) and a fluorescent monoclonal antibody against BrdU in combination with cytoplasmic staining for immunoglobulin (Ig). In 26 patients with monoclonal gammopathy (MG) the plasma cell labelling index (LI) as determined by this immunofluorescent method was compared with the tritiated thymidine (3H-TdR) LI. No difference in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…[3][4][5][6][7] "Traditional" methods for assessing proliferation in myeloma, i.e. 3 H-thymidine uptake, 3,8 bromodeoxyuridine uptake, [9][10][11] flow-cytometric cell-cycle analysis using propidium iodide 6 or assessment of Ki-67 expression, 12 did not find widespread use. This is mainly due to the not negligible effort involved in these methods, and the assumption that similar groups of patients could be identified either by conventional prognostic factors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] "Traditional" methods for assessing proliferation in myeloma, i.e. 3 H-thymidine uptake, 3,8 bromodeoxyuridine uptake, [9][10][11] flow-cytometric cell-cycle analysis using propidium iodide 6 or assessment of Ki-67 expression, 12 did not find widespread use. This is mainly due to the not negligible effort involved in these methods, and the assumption that similar groups of patients could be identified either by conventional prognostic factors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The PCLI is a slide-based immunofluorescence technique that uses antibodies against BrdU, which are incorporated into actively dividing plasma cells, thereby providing the percentage of plasma cells in the S-phase of the cell cycle. [6][7][8] Multiple authors have confirmed the independent prognostic value of an elevated PCLI of Ͼ 1%, which is predictive of shorter time to progression 9 and decreased survival. [10][11][12] To test our hypothesis, we studied 176 patients seen at Mayo Clinic between 1985 and 2005 with newly diagnosed myeloma who had a measurable PCLI of Ն 0.5%, which was obtained at time of diagnosis and again 4 months after initiation of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…
Mellstedt et al, 1984;Lokhorst et al, 1985). These findings suggested that the malignant transformation leading to the development of MM already occurred in a precursor of the plasma cell.
…”
mentioning
confidence: 84%
“…Neoplastic cells of transplanted murine plasmacytomas have been demonstrated to differentiate from small non-secreting clonogenic cells to large plasmacytoid cells secreting the homogenous Ig (Rohrer et al, 1977;Daley, 1981). In man, precursor cells expressing the myeloma idiotype in various stage of differentiation were demonstrated in the peripheral blood and in the BM (reviewed in Mellstedt et al, 1982;Mellstedt et al, 1984;Lokhorst et al, 1985). These findings suggested that the malignant transformation leading to the development of MM already occurred in a precursor of the plasma cell.…”
mentioning
confidence: 99%